2013
DOI: 10.1123/tsp.27.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the Long Jump Skill, Using Different Learning Techniques

Abstract: This study examined the contribution of instructional self-talk and observational learning on the development of long jump technique. Sixty-nine beginner athletes were randomly assigned to four groups: ‘self-talk’, ‘video’, ‘self-talk + video’ and control group. All groups performed 24 practice sessions, consisting of a cognitive intervention program in the form of either instructional self-talk or observational learning, or a combination of both, and the practice of specific drills. A significantly higher per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…Approach speed, also highly related to jumping distance (Hay, 1993), in our study represented by CG horizontal velocity at the instant of touch-down, had shown a maximal increase of 8.3 ± 9.2% for the Ve+Vi_BF group, with medium effect size (d = 0.62, p < 0.001), while Panteli et al (2013) reported small effect sizes for this variable. The control group also improved by 3.0 ± 5.2% (Figure 1.C) in their horizontal velocity, but the effect size was small (d = 0.27, p = 0.031).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Approach speed, also highly related to jumping distance (Hay, 1993), in our study represented by CG horizontal velocity at the instant of touch-down, had shown a maximal increase of 8.3 ± 9.2% for the Ve+Vi_BF group, with medium effect size (d = 0.62, p < 0.001), while Panteli et al (2013) reported small effect sizes for this variable. The control group also improved by 3.0 ± 5.2% (Figure 1.C) in their horizontal velocity, but the effect size was small (d = 0.27, p = 0.031).…”
Section: Discussionsupporting
confidence: 43%
“…Exercising without feedback consequently led to an increased approach speed because all groups received initial information before every single training session to run as fast as possible in their approach. Another possible explanation is that a linear relation between horizontal velocity and jumping distance in children also exists, but it is far weaker (r = 0.29), as reported by Panteli et al (2013).…”
Section: Discussionmentioning
confidence: 89%
“…For instance, observation of an actor responding to a sequence of stimuli has been found to result in immediate, short-term learning of the observed sequence [ 11 ] and the volume of learning accrued through action observation can be comparable to that achieved through physical practice alone [ 12 ]. Researchers have also demonstrated the effectiveness of action observation for the learning of complex motor skills including ballet [ 13 ], volleyball [ 14 ], football [ 15 ], cricket bowling [ 16 ] and long jumping [ 17 ]. Moreover, action observation has proven to be a useful complement to traditional stroke rehabilitation protocols [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The very nature of the long jump approach, which requires a near maximum speed and take-off accuracy on the board, characterizes this jumping event as a self-pacing, closed motor skill (Woods, 1998). Cognitive training, in the form of observational (Panteli et al, 2013) or blended learning (Kyriakidis et al, 2021), is shown to be beneficial for improvements in long jump performance. For individuals with intellectual impairment (II), the sensory, perceptive, cognitive, and learning deficits are linked with deficiencies at the perceptual, planning, and execution stages of motor performance.…”
Section: Introductionmentioning
confidence: 99%